Can Cover or Forage Crops Replace Fallow in the Semiarid Central Great Plains?. Issue 2 (1st March 2018) - Holman, Johnathon D.; Arnet, Kevin; Dille, Johanna; Maxwell, Scott; Obour, Augustine; Roberts, Tom; Roozeboom, Kraig; Schlegel, Alan
Abstract : Growing a crop in place of fallow may improve soil properties but result in reduced soil water and crop yields in semiarid regions. This study assessed the effect of replacing fallow in no‐till winter wheat ( Triticum aestivum L.)–fallow with cover, forage, or grain crops on plant available water (PAW), wheat yield, grain quality, and profitability over 5 yr, from 2007 to 2012. Plant available water at wheat planting was reduced the most when the fallow period was the shortest (i.e., following grain crops) or when biomass production was the greatest. Winter and spring lentil ( Lens culinaris Medik.) produced the least biomass, used the least soil water, and had the least negative effect on yield. For every 125 kg ha −1 of cover or forage biomass grown, PAW was reduced by 1 mm, and for every millimeter of PAW, wheat yield was increased by 5.5 kg ha −1 . There was no difference in wheat yield whether the preceding crop was harvested for forage or left as standing cover. In years with above‐average precipitation, wheat yield was reduced 0 to 34% by growing a crop in place of fallow. However, in years with below‐average precipitation, wheat yield was reduced 40 to 70% without fallow. There was minimal negative impact on wheat yield growing a cover or forage crop in place of fallow if wheat yield potential was 3500 kg ha −1 or greater. Net returns were reduced 50 to 100% by growing a cover crop. However, net returns were increased 26 to 240% by growing a forage crop. Integrating annual forages into the fallow period in semiarid regions has the greatest potential for adoption.